2011
DOI: 10.1177/0739456x11413602
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Home after Katrina

Abstract: In the aftermath of Hurricane Katrina, more than a million Gulf Coast residents were forced to flee, nearly 250,000 to Texas. New Orleans lost more than half its population. Four years later, many low-income residents had yet to return. Through qualitative research with low-income survivors relocated to Austin, Texas, and the caseworkers and service providers who worked with them, this article describes the experiences of low-income households. Disaster housing policies were a particularly poor fit for the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Further, housing recovery policies in the United States have structurally favored middle-class homeowners. Renters and lowincome homeowners' recovery needs have been insuffi ciently addressed (Fothergill & Peek, 2004;Kamel & LoukaitouSideris, 2004;Mueller, Bell, Chang, & Henneberger, 2011).…”
mentioning
confidence: 98%
“…Further, housing recovery policies in the United States have structurally favored middle-class homeowners. Renters and lowincome homeowners' recovery needs have been insuffi ciently addressed (Fothergill & Peek, 2004;Kamel & LoukaitouSideris, 2004;Mueller, Bell, Chang, & Henneberger, 2011).…”
mentioning
confidence: 98%
“…The most socially vulnerable populations, such as low-income and racial and ethnic minority groups, are less likely to have adequate insurance or the savings to rebuild. This is often due to historic housing policies and discriminatory processes in insurance and lending markets (Brody et al 2017; Cheung et al 2015; Peacock 1997; Zolfagharian et al 2020), and, on top of this, they face challenges in accessing governmental and nongovernmental aid, both of which slow their recovery (Delilah Roque, Pijawka, and Wutich 2020; Levine, Esnard, and Sapat 2007; Mitsova et al 2019; Mueller et al 2011; Paradee 2010). Other research has shown that even middle-class neighborhoods have difficulty recovering and accessing needed resources (Finch, Emrich, and Cutter 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the disaster research, including many vulnerability studies, focus on either neighborhood-level (Chakraborty, Collins, and Grineski 2019; D. Lee 2020; Peacock et al 2014; Zhang and Peacock 2010) or individual survivor experiences while displaced and trying to find housing (Johnson and Carswell 2021; Mueller et al 2011; Tafti and Tomlinson 2019; Weber and Peek 2012). Data on specifically fine-scale housing recovery, such as individual parcels, are rare because it is difficult and time-consuming to gather.…”
Section: Parcel-level Housing Disaster Researchmentioning
confidence: 99%
“…Discussions of community development have alternatively focused on community-based and equitable approaches to planning on one hand (Brand 2015; Rosen, O’Neill, and Hutson 2018; Sarmiento and Duarte 2015; Zapata and Bates 2017), or real estate, economic development, and housing policy on the other (Anacker and Niedt 2019; Cabrera and Najarian 2013; Kane and Weber 2016; Morales 2009; Mueller et al 2011). While not mutually exclusive, the two sides of community development’s representation in planning reflects often divergent understandings and approaches to the field that typically emphasize either “community” or “development” in community development practice.…”
Section: Community Development and Planning Educationmentioning
confidence: 99%
“…Some examples of a community emphasis include institutional analyses of comprehensive community initiatives that reflect the historical role that philanthropic organizations play in community capacity-building (Glickman and Servon 2003; Rosen, O’Neill, and Hutson 2018), while others draw attention to equity-based planning that leads to different and often uneven outcomes (Brand 2015; Sandoval 2018; Zapata and Bates 2017). Topics that emphasize development vary from assessments of housing policies and economic development tools (Anacker and Niedt 2019; Baxamusa 2008; Mueller et al 2011) to the economic and social benefits accrued from different approaches to development (Jamme et al 2019; Kane and Weber 2016; Lung-Amam, Pendall, and Knaap 2019; Nasar 2003).…”
Section: Community Development and Planning Educationmentioning
confidence: 99%